2022
DOI: 10.1002/cctc.202200684
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Ni Species Supported on Porous MgO during Ethanol Steam Reforming by XAS

Abstract: Operando time-resolved X-ray absorption spectroscopy (XAS) was used to determine nickel species supported on porous MgO during the ethanol steam reforming reaction. The Principal Component Analysis (PCA) of the nickel K-edge XAS spectra revealed Ni(OH) 2 , NiMgO, and metallic Ni during the activation and reaction of the catalysts. The Multivariate Curve Resolution-Alternating Least Squares (MCR-ALS) method for the timeresolved XAS spectra data permitted to calculate the concentration of species during the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The strong electrostatic interaction between Ni active phase and SiO 2 is conducive to form smaller Ni particle size and the enhancement of metal-support interaction, thus the Ni/SF-SEA exhibited higher catalytic activity and stability compared with Ni/SF catalysts prepared by impregnation and deposition precipitation methods. [115] The use of surfactant is a favorable et al [113,122] reported nano-crystalline MgO supported Ni catalyst prepared by using pluronic P123 and F127 as structure- [113] Reprinted with permission from Ref. [113] Copyright 2021 Elsevier.…”
Section: Modification Of Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong electrostatic interaction between Ni active phase and SiO 2 is conducive to form smaller Ni particle size and the enhancement of metal-support interaction, thus the Ni/SF-SEA exhibited higher catalytic activity and stability compared with Ni/SF catalysts prepared by impregnation and deposition precipitation methods. [115] The use of surfactant is a favorable et al [113,122] reported nano-crystalline MgO supported Ni catalyst prepared by using pluronic P123 and F127 as structure- [113] Reprinted with permission from Ref. [113] Copyright 2021 Elsevier.…”
Section: Modification Of Preparation Methodsmentioning
confidence: 99%
“…The use of surfactant is a favorable strategy to realize stable dispersion of active components and formation of mesoporous structure. Recently, Possato et al [113,122] . reported nano‐crystalline MgO supported Ni catalyst prepared by using pluronic P123 and F127 as structure‐directing agent.…”
Section: Catalyst Preparation Strategy For Esrmentioning
confidence: 99%